(2.5m + 1.5q)^2 (2.5m - 1.5q)^2
Answers
Answered by
3
Answer:
We have
(2.5m+1.5q)
2
=(2.5m)
2
+2(2.5m)(1.5q)+(1.5q)
2
[using (a+b)
2
=a
2
+2ab+b
2
]
=6.25m
2
+7.5mq+2.25q
2
(2.5m−1.5q)
2
=(2.5m)
2
−2(2.5m)(1.5q)+(1.59)
2
[using (a−b)
2
=a
2
−2ab+b
2
]
=6.25m
2
−7.5mq+2.25q
2
Therefore,
(2.5m+1.59)
2
+(2.5m−1.5q)
2
=(6.25m
2
+7.5mq+2.25q
2
)+(6.25m
2
−7.5mq+2.25q
2
)
=6.25m
2
+7.5mq+2.25q
+
6.25m
2
−7.5mq+2.25q
2
Collecting like terms,
=6.25m
2
+6.25m
2
+2.25q
2
+2.25q
2
+7.5mq−7.5mq
=12.50m
2
+4.50q
2
Step-by-step explanation:
pls mark me as brainlist
Similar questions